Knowledge, attitude, and proficiency of healthcare providers in cardiopulmonary resuscitation in a public primary healthcare setting in Qatar - Veettil, Shajitha Thekke; Anodiyil, Mohamed Shaheen; Khudadad, Hanan; Kalathingal, Mohamed Ali; Hamza, Abdul Hakeem; Ummer, Femina Purakaloth; Alnuaimi, Ahmed Sameer (Frontiers in Cardiovascular Medicine, 2023)
Introduction Early and effective Cardiopulmonary Resuscitation (CPR) increases both survival rate and post-cardiac arrest quality of life. This study aims to determine the current level of knowledge on, and ability to perform CPR among Physicians and Nurses in Health Centres (HCs) operated by the Primary Healthcare Corporation (PHCC) in Doha, Qatar. Methodology This study has two components: The first is a descriptive cross-sectional survey using an online form targeting physicians and nurses working in all HC’s. The aim was to assess their CPR knowledge and attitude. The second part is a direct observation of CPR drills to evaluate the skills and competencies of Code Blue Team (CBT) members in a convenient sample of 14 HCs. Results A total of 569 physicians and nurses responded to the survey. Only one-half 48.7% formally received training on basic life support in the last year, and 62.7% have tried to revive a dying person with no pulse. All the participants believe it is important to know how to revive a dying adult or child as part of their job. A multivariate model tested the independent effect of a set of explanatory variables on the total knowledge score. It showed that being a nurse was the most important predictor of a higher knowledge score. Attending more resuscitation courses (3-6 courses in the last 3-years) ranked second in importance, and a longer experience in clinical practice (5-10 and >10 years) ranked third in predictive power. In addition, the direct observation of CPR drill performance revealed a satisfactory outcome. Conclusion: The level of CPR knowledge and skills practice part of the health care providers in PHCC is deemed satisfactory as most providers reported having performed CPR in the past. Since PHCC is the first step to peoples’ health in Qatar, clinical staff should be certified and assessed regularly to ensure retention of resuscitation knowledge and skills.